Sediment transport modelling around bridge at Sungai Tuiusing 1D quasi unsteady flow HEC-RAS - Amaran, Krishnamuthi (2015)
Sungai Tui is located in the state of Pahang where huge amount of rainfall during monsoon season subjected to sediment transport process. The river responses by increased or decreased sediment carrying capacity, changing in channel cross section, erosion and deposition along the channel, which impact on river bank stability over a period of time. The research is to model sediment transport around bridge at Sungai Tui by using one dimensional (1D) quasi unsteady flow Hydrologic Engineering Centers River Analysis System (HEC RAS). There is few data required such as catchment area, precipitation data, geometric data and sediment data. The analysis is done using various method of transport function found in HEC RAS. For 5 years analysis of sediment transport, maximum erosion and deposition occurs at the depth 0.49m and 0.64m using Ackers-White; 0.50m and 0.76m using England-Hansen; 0.50m and 1.18m using Laursen; 0.50m and 1.12m using Meyer Peter Muller; 0.49m and 0.48m using Toffaleti; 0.50m and 0.76m using Yang and 0.50m and 1.18m using Wilcock. Erosion and deposition of sediment along the channel is not similar using various methods of transport function. In conclusion, sediment pattern can be predicted and analyzed using several methods in HEC-RAS software.